1991
DOI: 10.1111/j.1095-8649.1991.tb04389.x
|View full text |Cite
|
Sign up to set email alerts
|

Food habits, ontogenetic diet shift and selectivity in Zeus faber Linnaeus, 1758

Abstract: The feeding habits of Zeusfaber Linnaeus, 1758 were studied by examining digestive tracts in I2 size classes of individuals. It is a stenophagus species which begins life feeding almost exclusively on zooplankton until it is about 80 mm long, then switches gradually from zooplankton to small demersal fish, and finally when > 140 mm switches to feeding exclusively on benthic and demersal fish. Mysids were the most important food component in Z.faber < 141 mm and Cepola macrophrhalmu (Linnaeus, 1758) in Z . fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
4
7

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 35 publications
3
70
4
7
Order By: Relevance
“…Prey switching has been documented many times in a range of different systems (e.g. Stergiou & Fourtouni 1991, Aarnio et al 1996, Olson 1996, Dawe et al 1998, Merigoux & Ponton 1998, Manderson et al 1999, 2000, Scharf & Schlicht 2000. For example, predatory fish often change diet as alternative prey become available (e.g.…”
Section: What Constitutes 'Shallow Water'?mentioning
confidence: 99%
“…Prey switching has been documented many times in a range of different systems (e.g. Stergiou & Fourtouni 1991, Aarnio et al 1996, Olson 1996, Dawe et al 1998, Merigoux & Ponton 1998, Manderson et al 1999, 2000, Scharf & Schlicht 2000. For example, predatory fish often change diet as alternative prey become available (e.g.…”
Section: What Constitutes 'Shallow Water'?mentioning
confidence: 99%
“…Most available studies of the effects of ontogenetic niche shifts assume that individuals go through only a single ontogenetic niche shift during their life history , van de Wolfshaar et al 2006, Schreiber and Rudolf 2008, Guill 2009), whereas the life history of many top predators is characterized by the occurrence of multiple ontogenetic niche shifts (Winemiller 1989, Persson and Greenberg 1990, Stergiou and Fourtouni 1991, Flowers and Graves 1995, Lima 1998, Garcia-Berthou 2002, Martins et al 2002, Galarowicz et al 2006, Hammerschlag-Peyer and Layman 2012. The influence of two ontogenetic niche shifts in predator life history was studied in detail in a size-structured model analysis describing the life history of Atlantic cod (Gadus morhua; van Leeuwen et al 2013; see Plate 1) and was shown to result in a bottleneck in the prepiscivorous life stage (feeding on the intermediate resource), preventing predator population growth, and thereby also its top-down control of the prey fish species (van Leeuwen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The GI tract of herbivores is typically longer than that of carnivores and possesses specialized regions for the fermentation of plant material (Stevens and Hume, 1995;Karasov and Hume, 1997;Mackie, 2002). Equally apparent is how organisms are able to face routine fluctuations in the amount and type of food consumed due to seasonal changes in food availability, ontogenetic shifts in diet, reproductive status and alternating foraging and feeding strategies (O'Brien et al, 1989;Stergiou and Fourtouni, 1991;Koertner and Heldmaier, 1995;Johnson et al, 2001). In response to such shifts in feeding habits, and thus digestive demand, species modulate gut performance to match pace with digestive load (Hammond and Diamond, 1994;Piersma and Lindström, 1997;Weiss et al, 1998).…”
mentioning
confidence: 99%